Effectiveness of Joyful Learning Using Audio-Visual Media on Elementary Students' Learning Interest - Zossy Nofeanasari; Murdani, Eka; Wijaya, Andika Kusuma (Jurnal Gentala Pendidikan Dasar, 2025)
The Joyful Learning method is one of the teaching methods considered enjoyable for students. This method is assumed to be more effective in increasing students' learning interest compared to the direct instruction method. Therefore, this study aims to examine whether there is a difference in the average level of students’ learning interest between those taught using the Joyful Learning method and those taught using direct instruction, as well as to measure the effect size of the method on learning interest. This study employed a Quasi-Experimental Design approach. The sample consisted of 30 fifth-grade students from class V B, which served as the experimental group. The sampling technique used in this study was saturated sampling. Data were collected using a student learning interest questionnaire. The data analysis techniques used were the independent sample t-test and Effect Size. The results of the study indicate that: (1) Based on the independent sample t-test, the result shows a t-value of 4.762, which is greater than the t-table value of 2.0017 (4.762 > 2.0017), thus Hₐ is accepted and Hₒ is rejected. This indicates a significant difference in the average learning interest in IPAS (Social Sciences) between the class using the Joyful Learning method assisted by audio-visual media and the class using direct instruction. (2) The Effect Size value was found to be 1.3, which falls under the "very large effect" category. Therefore, it can be concluded that the Joyful Learning method assisted by audio-visual media has a significant impact on the learning interest of fifth-grade students at SD Negeri 5 Singkawang.